2018
DOI: 10.1039/c8an00148k
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituting donor T cells increase their biomass following hematopoietic stem cell transplantation

Abstract: In this study, we used a rapid, highly-sensitive, single-cell biomass measurement method, Live Cell Interferometry (LCI), to measure biomass in populations of CD3 + T cells isolated from hematopoietic stem cell transplant (SCT) patients at various times pre- and post-transplant (days 0-100). CD3 + T cell 'mass spectra' were obtained from five autologous and 20 allogenic transplant recipients. We found a pronounced rise in median T cell biomass (+25%; p <0.001) shortly after transplant (day 14), which moderated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…GSH is not necessary for cell activation, but activated T cells regulate their oxidative stress by using GSH, a key component for metabolic reprograming for cell differentiation [39]. Also, TCR ligation and binding with costimulatory molecules induces metabolic remodeling of the naive T cell to anabolic growth and biomass accumulation, and increases aerobic glycolysis [40].…”
Section: Discussionmentioning
confidence: 99%
“…GSH is not necessary for cell activation, but activated T cells regulate their oxidative stress by using GSH, a key component for metabolic reprograming for cell differentiation [39]. Also, TCR ligation and binding with costimulatory molecules induces metabolic remodeling of the naive T cell to anabolic growth and biomass accumulation, and increases aerobic glycolysis [40].…”
Section: Discussionmentioning
confidence: 99%
“…GSH is not necessary for cell activation, but activated T cells regulate their oxidative stress by using GSH, a key component for metabolic reprograming for cell differentiation 47 . TCR ligation and binding with costimulatory molecules induces metabolic remodeling of the naive T cell to anabolic growth and biomass accumulation, and increases aerobic glycolysis, even though sufficient oxygen is present to support glucose catabolism via the tricarboxylic acid cycle 30 . This phenomenon is termed the Warburg effect and also happens in proliferating cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that a dynamical systems model of T cell reconstitution may allow understanding alloreactivity in terms of antigenic differences between donors and recipients and ensuing T cell responses 2729 . This model incorporates the idea that when T cells become activated and undergo metabolic changes upon antigen encounter, they may increase mass, and this appears to be the case when T cell masses are measured following allogeneic SCT 30 . This change in mass is likely driven by the cytokine and chemokine milieu in these patients, which is likely to be altered because of conditioning chemotherapy and radiation induced tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, QPI measurements of reconstituting donor T cells following hematopoietic stem cell transplantation showed mass changes correlated with immune reconstitution within the first few weeks post-transplant, a finding which could guide the withdrawal of immunosuppressive drugs and reduce the likelihood of graft-versus-host disease or cancer relapse. 207 In studies of B lymphocytes, QPI measurements also uncovered rapid mass accumulation and cell proliferation within the first 24 h of B cell activation accompanied by sustained AMP-kinase activation in the absence of energetic stress, an unexpected result because AMP-kinase activity strongly opposes anabolism and constrains mass accumulation in most biological contexts. 208 QPI was also used to measure variability in nai ̈ve B cell size and partitioning of mass between daughter cells during B cell expansion, providing support for an in silico model suggesting that intrinsic biological noise plays a key role in determining the extent of B cell proliferation, which ultimately determines which cells contribute to an immune response.…”
Section: Advances In Quantitative Biologymentioning
confidence: 99%